simplify the given polynomial and use it to complete the statement. (8×2-5x-7)-(9×2-3x-5)+(x+7)(x+1)

Question

simplify the given polynomial and use it to complete the statement. (8×2-5x-7)-(9×2-3x-5)+(x+7)(x+1)

in progress 0
Adeline 3 weeks 2021-10-01T15:40:23+00:00 1 Answer 0

Answers ( )

    0
    2021-10-01T15:41:24+00:00

    Answer:

    6x+5

    Step-by-step explanation:

    (8x^2-5x-7)-(9x^2-3x-5)+(x+7)(x+1)=

    8x^2-5x-7-9x^2+3x+5+x*x+x*1+7*x+7*1=

    -x^2 – 2x-2+x^2 +x+7x+7=

    -2x-2+8x+7=6x+5

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )